NILAI-NILAI PENDIDIKAN AKHLAK KEPADA KAUM DHUAFA (Perspektif Al-Qur’an Surat An-Nisa Ayat 36 Tafsir Al-Maraghi) - Sapto Wardoyo; Ahmad Mukhlasin; Abdullah Ridlo (STAI Sufyan Tsauri Majenang, 2020)
: In Islam it self has been taught about moral education for humans that is contained in the life guidelines of Muslims, namely in the al-Qur'an and al-Hadith. In the Koran, there is a lot of explanation regarding moral education that must be studied and also carried out by humans in everyday life with the aim of creating a generation of noble morals as contained in the Qur'an surah An-Nisa verse 36. Morals include all aspects of human life in accordance with their position as individual beings, social creatures, human beings who live in nature, and as God's creatures. The formulation of the problem in this research is how the values of moral education for the poor that are contained in the Al-Qur'an Surah An-Nisa verse 36 Tafsir Al-Maraghi. The aim is to find out the values of moral education for the poor in Q.S An-Nisa verse 36, to provide information and knowledge to the public regarding the values of moral education contained in Q.S An-Nisa verse 36. This type of research in this thesis is library research (library research) with the research approach used is a qualitative approach. This research was conducted by reading literature books related to the discussion of this thesis. The results of the author's research on the values of moral education for the poor, the perspective of the Qur'an, Surah An-Nisa verse 36 Tafsir Al-Maraghi is that the values of moral education for the poor are contained in QS An-Nisa verse 36 which in this case the morals of the dhuafa consist of several values of moral education, namely: (1) morals towards the dhuafa, (2) the rights of the dhuafa, (3) prohibition of the dhuafa.